The validity of ergometer testing in rowing - Payne, W. (National Sports Research Centre, 1996)
There is considerable debate on the relevance of measuring blood lactate concentrations in athletes, and about the appropriate way of expressing the results for the use of coaches who are monitoring training. This study examines the validity of blood lactate profiles obtained during rowing ergometry for use in monitoring training and in setting on-water training intensities.